Makna Simbolis dalam Tradisi Maccera' Tappareng di Danau Tempe Kabupaten Wajo - Kamaruddin Mustamin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
Maccera' tappareng tradition, as the part of culture heritage from Buginese decendant has symbolic meaning practically and also theoritically, especially for fishermen community at Tempe lake. Practically, symbolic meaning can be seen on: sacrifice ceremony namely to sink a buffalo’s head in the middle of Tempe lake; the special way in sacrificing buffalo’s head to the king of lake (punna wae) which is only known by maccua tappareng; the presentation of walasuji (the name of sacrifice tools) equipments which being a place for putting buffalo’s head and also the others sacrifice; the drum music which become a special code in the running the tradition of maccera’ tappareng; the formation of rules about the obligation and the prohibition which should be obeid by the fishermen. In cultural area, maccera' tappareng tradition is the descedant culture heritage which should be kept everlasting as local culture resources. Maccera’ tappareng tradition has role in keeping Tempe lake ecosystem and social cohesion of fishermen community